Formulasi dan Uji Stabilitas Sediaan Suspensi Ekstrak Rimpang Zingiber zerumbet - Shavira, Shafa; Margaretta, Angel Dineta; Sandra, Aprilia Dwi; Sitorus, Raya Uli; Fatmaria, Fatmaria (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
Zingiber zerumbet (L) SmithÂ rhizomeÂ has been used traditionally as an herbal medicine in Indonesia. Isolated extracts and metabolites ofÂ Z. zerumbetÂ have shown anti-inflammatory, antioxidant, antidiabetic, anticancer, antimicrobial, analgesic and antiviral activity. TheÂ form of suspensionÂ is carried out to facilitate the utilization of the main bioactive content, zerumbone, which is difficult to dissolve in water. TheÂ formulation of suspensionÂ is based on variations in the concentration ofÂ Z. zerumbetÂ extract, which is 2.5% (formulation 1), 5% (formulation 2), and 10% (formulation 3). ToÂ determine theÂ physical stability, the evaluation is carried out, namely: organoleptic test, density, viscosity, redispersibility and pH.Â The resultsÂ showed all three formulations did not provide organoleptic changes for 30 days, >1 g/cm3 density, good redispersibility, and pHÂ ofÂ 6. The viscosity of each formulation is quite varied i.e., 3.74 cp; 4,27 cp; and 11.8 cp.Â Formulation 3 is determined as the best formulation based on its viscosity which is closest to the standard range of good suspension viscosity according to the SNI.